Analysis of the Impact of E-Commerce Utilization, Digital Entrepreneurship, and Product Branding on MSME Customer Loyalty in West Java - Mohammad Gifari Sono; Andry Stepahnie Titing; Ellys Nurhaliza (Westscience Press, 2024)
This study examines the impact of Digital Entrepreneurship, E-Commerce Utilization, and Product Branding on MSME Customer Loyalty in West Java. A quantitative approach was employed with a sample of 200 MSME owners and customers, using a Likert scale (1-5) for data collection and Structural Equation Modeling - Partial Least Squares (SEM-PLS) for analysis. The results reveal that all three factors significantly influence customer loyalty, with E-Commerce Utilization having the strongest effect followed by Digital Entrepreneurship and Product Branding. These findings suggest that MSMEs that leverage digital platforms, adopt innovative business models, and establish strong brands are more likely to enhance customer satisfaction and loyalty. The study underscores the importance of integrating digital tools, e-commerce strategies, and branding in MSME operations to foster long-term customer relationships and competitiveness in the market.